Organic semiconductor photodiode based on indigo carmine/n-Si for optoelectronic applications - Ganesh, V.; Manthrammel, M. Aslam; Shkir, Mohd.; Yahia, I. S.; Zahran, H. Y.; Yakuphanoğlu, Fahrettin; AlFaify, S. (Springer, 2018)
The fabrication of indigo carmine/n-Si photodiode has been done, and a robust dark and photocurrent-voltage (I-V), capacitance vs. voltage (C-V) and conductance vs. voltage (G-V) studies were done over a wide range of applied voltage and frequencies. The surface morphology was assessed by atomic force microscope (AFM), and the grain size was measured to be about 66 nm. The reverse current increased with both increasing illumination intensity and bias potential, whereas the forward current increased exponentially with bias potential. The responsivity value was also calculated. Barrier height and ideality factor of diode were estimated through a vs plot, and obtained to be 0.843 and 4.75 eV, respectively. The V-bi values are found between 0.95 and 1.2V for frequencies ranging between 100 kHz and 1 MHz. The value of R (s) is found to be lower at higher frequencies which may be due to a certain distribution of localized interface states. A strong frequency and voltage dependency were observed for interface states density N (ss) in the present indigo carmine/n-Si photodiode, and this explained the observed capacitance and resistance variation with frequency. These results suggest that the fabricated diode has the potential to be applied in optoelectronic devices.
Keywords: Series Resistance; Devices; Fabrication; Constant; Contacts; Polymer; Diodes; Light